Communicating Food Risk-Benefit Assessments: Edible Insects as Red Meat Replacers - Boehm, Emilia; Borzekowski, Dan; Ververis, Ermolaos; Lohmann, Mark; Böl, Gaby-Fleur (Frontiers in Nutrition, 2021)
Risk-benefit Assessment (RBA) is an emerging methodology in the area of Food and Nutrition that offers a simultaneous evaluation of both risks and benefits linked to dietary choices. Communication of such research to consumers may present a challenge due to the dual nature of RBA. We present a case study of a communication strategy developed for the NovRBA-project. The NovRBA-project (Novel foods as red meat replacers – an insight using Risk Benefit Assessment methods) performed a risk-benefit assessment to evaluate the overall health impact of substituting red meat (beef) by a novel food (house cricket), considering the microbial, toxicological and nutritional characteristics of the respective dietary choices. A literature review of risk perceptions and acceptance of beef and insects as food formed the basis of the communication strategy for the study’s results, drawing on environmental and emotional as well as health-related motivations to consume or avoid either food and considering the sociodemographic characteristics of likely consumers. Challenges and future directions for consumer protection organisations communicating findings of risk-benefit analyses on food safety are discussed.